Specific tension index of elbow flexors in trained and untrained men - Thiago Torres Matta; Belmiro Freitas Salles; Juliano Spinetti; Roberto Simão; Liliam Fernandes Oliveira (Universidade Federal de Santa Catarina, 2010)
The specific tension index (STI) estimates the ratio of maximum torque (TQ) to muscle volume (MV) for a specific task and includes muscle thickness as a parameter, which can be directly evaluated by ultrasound. The objective of the present study was to compare TQ, MV and STI of the elbow flexors between strength-trained and untrained subjects. Forty men, including 11 subjects strength trained for at least two years [trained group (TG): 23.5 ± 3.1 years; 182.1 ± 4.9 cm; 88.1 ± 8.4 kg] and 29 untrained subjects [untrained group (UG): 29.8 ± 1.6 years; 172.4 ± 6.6 cm; 76.4 ± 8.1 kg], participated in the study. The STI of the elbow flexors, expressed as the TQ/MV ratio, was calculated for both groups. Muscle thickness measured by ultrasound was used to estimate MV. TQ of the elbow flexors was estimated using maximum isometric voluntary contractions. The Mann-Whitney test was used to determine possible differences in TQ, STI and MV between groups. MV and TQ were significantly higher in TG (526.07 ± 86.13 cm3; 112.04 ± 24.18 Nm) than UG (385.40 ± 80.89 cm3; 88.46 ± 13.77 Nm). There was no significant difference in the STI between TG (0.213 ± 0.03 Nm.cm3-) and UG (0.233 ± 0.02 Nm.cm3-). Although stronger, trained subjects presented elbow flexor STI values similar to those of the untrained group, a finding suggesting the maintenance of the linearity of the force-volume ratio. TQ and MV estimates were found to be reliable parameters for the distinction between groups. The STI may contribute to a more applied analysis in clinical practice and in the prescription of physical activity as an indicator of inadequate levels of overload and of the risk of injury.